The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.4161/cbt.7.9.6418
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible proto-oncogene Pim-1 is a prognostic marker in pancreatic ductal adenocarcinoma

Abstract: Background: Pim-1 is a proto-oncogene involved in cell survival, differentiation and proliferation in several hematologic and epithelial malignancies. Clinically, absence of Pim-1 expression correlates with poor prognosis in prostate cancer. In the present study, the expression of Pim-1 is analyzed in pancreatic cancer and correlated to clinicopathological parameters.Results: Compared to benign, inflammatory and pre-malignant conditions (i.e., the normal pancreas, chronic pancreatitis and benign intraductal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 27 publications
(49 reference statements)
2
73
0
Order By: Relevance
“…In agreement with these data are the up-regulation of cMYC and VEGF in human cord blood CD34 ϩ cells by STAT5 in an HIF2␣-dependent manner. Although so far PIM1 has only been described as a HIF1␣ target gene, 36,37 we do find that PIM1 is also up-regulated in STAT5-transduced HSCs. In addition to the growthpromoting activity of these genes, it has been suggested that HIF2␣ might contribute to the growth of tumor cells via activation of EGFR and IGFR1 tyrosine kinases.…”
Section: Discussionmentioning
confidence: 44%
“…In agreement with these data are the up-regulation of cMYC and VEGF in human cord blood CD34 ϩ cells by STAT5 in an HIF2␣-dependent manner. Although so far PIM1 has only been described as a HIF1␣ target gene, 36,37 we do find that PIM1 is also up-regulated in STAT5-transduced HSCs. In addition to the growthpromoting activity of these genes, it has been suggested that HIF2␣ might contribute to the growth of tumor cells via activation of EGFR and IGFR1 tyrosine kinases.…”
Section: Discussionmentioning
confidence: 44%
“…105 In addition, increased PIM1 expression was proposed to be a prognostic marker for pancreatic ductal adenocarcinoma. 106 Tumor-associated hypoxia seems to increase PIM1 expression and to support chemoresistance shown in several solid cancer cell lines. 107 These observations suggest that targeting of PIM1 might be beneficial in combination with chemotherapeutics for the therapy of solid cancers.…”
Section: Solid Tumorsmentioning
confidence: 98%
“…Immunohistochemistry was performed using the Dako Envision System, as published previously (22). Briefly, consecutive paraffin-embedded tissue sections (3 μm thick) were deparaffinized and rehydrated using routine methods.…”
Section: Reagentsmentioning
confidence: 99%
“…Semiquantitative analysis was performed as published previously (22). Scores were given separately for the stained area and for the intensity of staining.…”
Section: Semi-quantitative Analysis Of Grp94 Expression In Tissuesmentioning
confidence: 99%